ANALISIS TECHNOLOGY ACCEPTANCE MODEL (TAM) PADA IMPLEMENTASI E-KATALOG DALAM MENDUKUNG PROGRAM ZERO CORRUPTION DI AKADEMI MILITER - Pramudita, Nadya Sekar; Prapsetyo, Agung; Lestari, Kiki (PPM Sdirjianbang Akademi Militer, 2025)
Corruption in the procurement of goods and services is a serious problem that occurs not only in the civilian sector but also in the military environment. One concrete effort to suppress corrupt practices is to utilize a digital system in the procurement of goods and services through the e-Catalog. This study aims to analyze the implementation of the e-Catalog in supporting the zero corruption program at the Military Academy using the Technology Acceptance Model (TAM) approach, which emphasizes two main variables: perceived usefulness and perceived ease of use. The study was conducted using a descriptive qualitative method through interviews and observations of personnel involved in the procurement process. The results show that the use of the e-Catalog can increase efficiency, transparency, and accountability, thereby supporting the strengthening of organizational integrity. However, successful implementation still faces challenges such as limited digital infrastructure and technological literacy among users. Overall, the e-Catalog is considered effective as a modern procurement tool that supports clean and accountable governance in the military environment.